Evaluation of different chemical fungicides against rice blast in field conditions - Moktan, Rachana; Aryal, Anjeela; Karki, Sagar; Devkota, Ashbin Kumar; Acharya, Basistha; Joshi, Darbin; Aryal, Krishna (Journal of Agriculture and Natural Resources, 2021)
Evaluation of different fungicides against rice blast was carried out in research plot of the Agronomy farm of IAAS, Prithu Technical College, Lamahi Municpality, Dang district of the Lumbini Province, inner terai region of Nepal during June to November, 2017. The objective of the experiment was to evaluate the efficiency of different chemical fungicides against rice blast. The experiment was conducted in Randomized Complete Block Design with the use of susceptible variety ‘Mansuli’. Different fungicides like Hexaconazole 5% SC (Udaan), Propiconazole 25% EC (Tilt), Captan 70% + Hexaconazole 5% WP, Validamycin 3% L, Tricyclazole 75% WP (TRIP) and Biomycin (Kasugamycin 3% S.L.) were applied five times at weekly interval with the doses of 2mL/L of H2O, 1.5mL/L of H2O, 2g/L of H2O, 2mL/L of H2O, 2g/L of H2O and 2mL/L of H2O respectively. From the result, it was concluded that all the fungicides were effective in controlling leaf blast but Tricyclazole 75% WP (TRIP) was more effective among other fungicides and untreated control plots with least leaf blast severity (27.85%), least incidence (35.5%), least mean AUDPC (64.64%) and highest grain yield (3.93 t ha-1) followed by Biomycin. It is thus concluded that fungicide Tricyclazole 75% WP should be sprayed five times at weekly interval for the management of leaf blast in rice.